DEVELOPMENT OF MEDIA BASED ON GENDER AWARENESS AMONG ELEMENTARY SCHOOL STUDENTS - Wahyudi, Agus (DIVERSITY Logic Journal Multidisciplinary, 2024)
Background. Gender education in education circles often tends to be neglected by parents and the community. This happens because the community does not realize how important gender-awareness-based education is for children at the elementary education level as a provision for children to know their identity when they are adults. Research Purpose. The purpose of this study is to create gender-awareness-based learning media that can be integrated with learning in elementary school educational institutions and carried out with the help of parents. Research Method. Researchers use the Research and Development development research model with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data analysis technique for this study comes from data from instrument validation results, namely descriptive data from material, language, media, and media implementation experts. Findings. The findings in this study are that interactive edutainment media is feasible and contains an introduction to gender identity. In addition, the introduction of gender insight that is intended to be developed for elementary school students through this book is an understanding of the biological function of sex, body parts, introduction to genitals, and gender roles. Conclusion. Gender education in education circles often tends to be neglected by parents and the community. This happens because the community does not realize how important gender-awareness-based education is for children at the elementary education level as a provision for children to know their identity when they are adults.